Acanthephyra quadrispinosa Kemp 1939 ... - D'Acoz, Cédric D'Udekem; Degrave, Sammy (Zenodo, 2018)
Acanthephyra quadrispinosa Kemp, 1939 A widely distributed pelagic waters species; only once encountered in the Indian sector of the sub-Antarctic AOI: 45°53'S, 84°33'E (Hale 1941) and once in the East Pacific sector of the sub-Antarctic AOI (Wasmer 1986); also off southern Australia (Wasmer 1993). ... : Published as part of D'Acoz, Cédric D'Udekem & Degrave, Sammy, 2018, A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps, pp. 201-240 in Zootaxa 4392 (2) on page 217, DOI: 10.11646/zootaxa.4392.2.1, http://zenodo.org/record/1195302 ...